“It Is Tough to Come Back. Who Am I Now as a Language Teacher?”: The Re-Positioning of Three Vietnamese Teachers of English Language Returning from Overseas Programs - Vu, Ngoc Tung; Dinh, Hanh (Journal of Ethnic and Cultural Studies, 2024)
Theoretically grounded in positioning theory, this study aimed to unpack three stories of Vietnamese teachers of English’ transformation of teaching theory and practice due to their international and intercultural overseas experiences. Our ethnography study was centered on those teachers’ varying perceptions of what and how to teach. Our examination of the teacher candidates’ written critical reflection and interview was conducted over one year after they returned to teach in Vietnam. Particularly, these teachers’ perceived teaching and learning changes were a possible consequence of their experiences of intercultural engagement in many local settings in their host countries where they had previously stayed before returning. Using positioning and transformative learning as a theoretical lens, the researchers explored how teachers’ transformation was revealed after their return, suggesting that there were themes of positioning, including their modified cognition, awareness, attitudes, and behavior. More specifically, the findings implied that educational nation-level and school-level policy should pay more attention to the local English teachers’ privileges and threats that drive how they navigate their professional careers, considering academic qualifications and personal attributes. While the former was related to implications for teacher education programs (that help them identify teaching philosophy, methodology, and teaching environments), the latter involved teacher characteristics, aspirations, and accumulated capital.